Histological Study of the Immune System in Zebrafish, Danio Rerio (Hamilton, 1822) - Azar Azin (Sciendo, 2021)
The aim of the present study was to investigate the cellular characteristics of the immune tissues of Zebrafish, Danio rerio (Hamilton, 1822). The fish were fixed in Bouin՚s solution for 24 hours then dehydrated, cleared, paraffinized, embedded and finally sectioned, stained and observed through optical microscopy. Results showed that immune system tissues of Zebrafish include the apical part of the kidney, thymus, and spleen. The apical part of the kidney was composed of hematopoietic tissue containing blood and immune cells. The spleen was a single organ located at the abdominal cavity containing melanomacrophages. The thymus was observed as a paired organ at the posterior part of the branchial cavity. Results showed that the immune system of the Zebrafish was dispersed in several organs of the body and that this species could be used as a laboratory model organism in immune system studies.